THE ROLE AND PROSPECTS OF TEACHING MATHEMATICAL MODELING IN THE DIGITAL LEARNING ENVIRONMENT OF HIGHER EDUCATION - Narzullayeva, Feruza; Khusniddin Jurayev (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to explore the content and pedagogical approaches of the "Mathematical Modeling" course in higher education and to analyze its adaptation to the digital learning environment. The objective is to identify effective methods to enhance students' modeling skills using modern technologies. Method: A mixed-method approach was employed, combining a literature review, content analysis of current curricula, and a survey among educators and students from universities in Uzbekistan. Additionally, case studies of digital platforms and e-learning tools integrated into the "Mathematical Modeling" course were analyzed. Results:Findings indicate that integrating digital tools—such as interactive simulations, mathematical software, and online assessment platforms—significantly improves student engagement and understanding of abstract modeling concepts. Educators also reported increased flexibility and efficiency in course delivery. Novelty:The study provides a comprehensive model for digitally transforming the "Mathematical Modeling" course, tailored to the context of Central Asian higher education. It introduces a structured digital pedagogy framework that balances theoretical knowledge with interactive practice, thus offering new insights for curriculum developers and policymakers.